How can we quantitatively study insects whose larvae live beneath the forest floor? A case study at an experimental long‐term log‐removal site in Japan. Issue 3 (28th June 2019) - Tsunoda, Tomonori; Hyodo, Fujio; Sugiura, Daisuke; Kaneko, Nobuhiro; Suzuki, Satoshi N.
Abstract: This study quantified the numbers and sex ratio of adult Sericania hidana (Coleoptera: Scarabaeidae) in a subalpine forest in 2017. Data from an area littered with coarse woody debris (CWD) created by a typhoon in 1959 were compared with those from an area where CWD had been cleared by salvage logging. Three types of traps were used: flight interception traps (FITs) with a black light, pitfall traps (PITs), and soil emergence traps (SETs). Carbon and nitrogen stable isotopes were analyzed to evaluate S. hidana diets and habitats. Overall, there were more S. hidana in the unsalvaged sites than in the salvaged sites. The FITs captured only males but SETs captured both males and females. The SETs on CWD captured more S. hidana than did SETs on soil in both the salvaged and unsalvaged sites. The PITs captured only a few individuals; thus, PITs are not suitable for studying this insect, although such traps were previously reported to capture S. hidana adults. Stable isotope analyses suggested that S. hidana feeds on a variety of plant materials, including living plants and CWD. These results suggest that CWD has long‐term effects on insect populations. Soil emergence traps provide an effective method to quantitatively evaluate insect ecology, and FITs can effectively screen for the existence of insects. Abstract : Coarse woody debris created in 1959 has long‐term effects on populations of Sericania hidana (Coleoptera; Scarabaeidae). Soil emergence traps provide an effective method to quantitatively evaluate insect ecology, and flight interception traps can effectively screen for the existence of insects.